Understanding e-government technology transfer: evidence from the transfer of a patent management system from EPO to INPI - Cavalheiro, Gabriel Marcuzzo do Canto (2014)
Drawing upon Brazilian experience, this research explores some of the key issues to be addressed in using e-government technical cooperation designed to enhance service provision of Patent Offices in developing countries. While the development of software applications is often seen merely as a technical engineering exercise, localization and adaptation are context bounded matters that are characterized by many entanglements of human and non-humans. In this work, technical, legal and policy implications of technical cooperation are also discussed in a complex and dynamic implementation environment characterized by the influence of powerful hidden agendas associated with the arena of intellectual property (IP), which are shaped by recent technological, economic and social developments in our current knowledge-based economy. This research employs two different theoretical lenses to examine the same case, which consists of transfer of a Patent Management System (PMS) from the European Patent Office (EPO) to the Brazilian Patent Office that is locally named ‘Instituto Nacional da Propriedade Industrial’ (INPI). Fundamentally, we have opted for a multi-paper thesis comprising an introduction, three scientific articles and a concluding chapter that discusses and compares the insights obtained from each article. The first article is dedicated to present an extensive literature review on e-government and technology transfer. This review allowed the proposition on an integrative meta-model of e-government technology transfer, which is named E-government Transfer Model (ETM). Subsequently, in the second article, we present Actor-Network Theory (ANT) as a framework for understanding the processes of transferring e-government technologies from Patent Offices in developed countries to Patent Offices in developing countries. Overall, ANT is seen as having a potentially wide area of application and being a promising theoretical vehicle in IS research to carry out a social analysis of messy and heterogeneous processes that drive technical change. Drawing particularly on the works of Bruno Latour, Michel Callon and John Law, this work applies this theory to a longitudinal study of the management information systems supporting the Brazilian Patent Office restructuration plan that involved the implementation of a European Patent Management System in Brazil. Based upon the ANT elements, we follow the actors to identify and understand patterns of group formation associated with the technical cooperation between the Brazilian Patent Office (INPI) and the European Patent Office (EPO). Therefore, this research explores the intricate relationships and interactions between human and non-human actors in their attempts to construct various network alliances, thereby demonstrating that technologies embodies compromise. Finally, the third article applies ETM model as a heuristic frame to examine the same case previously studied from an ANT perspective. We have found evidence that ETM has strong heuristic qualities that can guide practitioners who are engaged in the transfer of e-government systems from developed to developing countries. The successful implementation of e-government projects in developing countries is important to stimulate economic growth and, as a result, we need to understand the processes through which such projects are being implemented and succeed. Here, we attempt to improve understanding on the development and stabilization of a complex social-technical system in the arena of intellectual property. Our preliminary findings suggest that e-government technology transfer is an inherently political process and that successful outcomes require continuous incremental actions and improvisations to address the ongoing issues as they emerge.